2020
DOI: 10.48550/arxiv.2005.07210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LAMOST Medium-Resolution Spectroscopic Survey (LAMOST-MRS): Scientific goals and survey plan

Abstract: Since September 2018, LAMOST starts a new 5-year medium-resolution spectroscopic survey (MRS) using bright/gray nights. We present the scientific goals of LAMOST-MRS and propose a near optimistic strategy of the survey. A complete footprint is also pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
119
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

6
3

Authors

Journals

citations
Cited by 84 publications
(119 citation statements)
references
References 57 publications
0
119
0
Order By: Relevance
“…The MRS has R ∼ 7500 and includes both a blue arm (B) and a red arm (R). Spectral observations made from the blue arm spanning wavelength in a range of 4950 ∼ 5350 Å and the spectra observed using the red arm cover a wavelength range of 6300 ∼ 6800 Å (Liu et al 2020). LAM-OST finished the first observing campaign from 2011 to 2018 (known as LAMOST I).…”
Section: Lamost Data Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MRS has R ∼ 7500 and includes both a blue arm (B) and a red arm (R). Spectral observations made from the blue arm spanning wavelength in a range of 4950 ∼ 5350 Å and the spectra observed using the red arm cover a wavelength range of 6300 ∼ 6800 Å (Liu et al 2020). LAM-OST finished the first observing campaign from 2011 to 2018 (known as LAMOST I).…”
Section: Lamost Data Selectionmentioning
confidence: 99%
“…The second active survey program (LAMOST II) began in 2017 September. A total number of about five million medium-resolution spectra observed with a single exposure for ∼800,000 stars were collected by 2019 June (Liu et al 2020). Liu et al (2019) identified 16,032 early-type stars through measuring the equivalent widths of several absorption line profiles using low-resolution spectra from the LAMOST LRS database.…”
Section: Lamost Data Selectionmentioning
confidence: 99%
“…The LAMOST MRS-N, (Wu et al, 2020;Wu et al, 2021), as a sub-project of the Medium-Resolution Spectral Survey (MRS, (Liu et al, 2020)), mainly relies on the LAMOST (also known as Guoshoujing Telescope), which is the first astronomical large-scale scientific facility of China (Cui et al, 2012;Zhao et al, 2012;Wang et al, 1996;Su & Cui, 2004) and has achieved great success in many fields of astronomy (Liu et al, 2020;Gao et al, 2014;Liu et al, 2015;Karoff et al, 2016;Luo et al, 2016;Wang et al, 2017b;Ren et al, 2018b;Liu, 2019;Liu et al, 2019;Gu et al, 2019;Wu et al, 2016Wu et al, , 2020Tian et al, 2015;Xiang et al, 2015a;Huang et al, 2016;Liu et al, 2017a,b;Tian et al, 2017;Wang et al, 2017a;Li et al, 2018;Tian et al, 2018;Wang et al, 2018;Xu et al, 2018;Yu & Liu, 2018;Zhao et al, 2018;Li et al, 2019;Tian et al, 2019;Wang et al, 2019b,a;Shen et al, 2016;Wu et al, 2010a,b;Huang et al, 2019), to observe the nebulae (including the H II regions, Herbig-Haro objects, supernova remnants, planetary nebulae) in the northern Galactic Plane (GP). From October 2018 to now, MRS-N has been conducted for three years and obtained more than 190 thousand medium resolution spectra of Galactic nebulae.…”
Section: Introductionmentioning
confidence: 99%
“…The LAMOST medium-resolution survey (MRS, R ∼ 7 500, Liu et al 2020), started from Sep. 2017, is one of the pioneer time-domain spectroscopic surveys. The blue and red arms cover Mg b triplet (4950−5350 Å) and Hα (6300−6800 Å), respectively.…”
Section: Introductionmentioning
confidence: 99%